Early angiographic signs of acute thrombus formation following cerebral aneurysm treatment with the Pipeline embolization device. (21st October 2016) - Patel, Akil; Miller, Timothy R; Shivashankar, Ravi; Jindal, Gaurav; Gandhi, Dheeraj
Abstract : Background and objective: Acute thrombus formation following aneurysm treatment with the Pipeline embolization device (PED) is a potentially devastating complication that may result in significant thromboembolic sequelae if not promptly treated. We therefore evaluated PED cases complicated by acute thrombus formation at our institution, with an emphasis on identifying early angiographic signs that may portend this event. Materials and methods: We retrospectively identified cases of acute thrombosis following PED placement in 100 consecutive procedures performed at our institution from a prospectively maintained clinical database. Angiographic findings were analyzed for early signs of acute thrombus formation. We also evaluated the efficacy of treatment of this complication with a glycoprotein IIb/IIIa inhibitor (abciximab), as well as the results of pre-procedure platelet inhibition testing. Results: Acute thrombus formation was encountered in five patients following PED placement (5%). Early angiographic signs were present in all cases and included progressive stagnation of blood flow in covered side branches, occlusion of covered side branches, excessive stagnation of blood flow in the target aneurysm, as well as occlusion of the target aneurysm. These sequelae completely resolved following abciximab treatment in all five cases, with no permanent neurological morbidity or mortality. Four of the five patients had a pre-procedure P2Y12 value >200 (range 201–227). Conclusions: Progressive stagnation or occlusion of covered side branches or target aneurysm are early angiographic signs of acute thrombus formation following PED placement and should prompt immediate treatment with a glycoprotein IIb/IIIa inhibitor. Platelet inhibition testing may help identify those patients who are at an increased risk for this complication.